Rapid and Efficient Method to Make Competent Bacterial Cells for Genetic Transformation - Siamalube, Beenzu; Ehinmitan, Emmanuel; Ngotho, Maina; Onguso, Justus; Runo, Steven (International Journal of Membrane Science and Technology, 2024)
There is absence of natural occurrence of genetic transformation in many bacteria due to the negative charges of DNA and bacteria, hence the DNA must be forced into the bacterial cells. Escherichia coli is mainly the host of choice because of its simplistic genetic mechanism and readily available molecular biological tools to inexpensively cultivate it. After the bacterial cells are made competent, it is anticipated that they contain and express the gene of interest that is cloned in the plasmid they take up during transformation. The Polymerase Chain Reaction method is then used to determine the presence of the gene and identify the band size, thereof. This paper will tabulate the step-by-step protocol of making competent E. coli cells strain K12 using calcium chloride solution and the heat-shock method and outline the procedure to confirm the positive transformants.